2018
DOI: 10.12659/msm.910016
|View full text |Cite
|
Sign up to set email alerts
|

miR-106a Reduces 5-Fluorouracil (5-FU) Sensitivity of Colorectal Cancer by Targeting Dual-Specificity Phosphatases 2 (DUSP2)

Abstract: Background5-Fluorouracil (5-FU)-based chemotherapy is a conventional therapeutic approach for the treatment of patients with colorectal cancer (CRC). However, development of 5-FU resistance frequently occurs. We explored a potential method for regulating the sensitivity to 5-FU-based chemotherapy in CRC patients.Material/MethodsCell viability was determined by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide (MTT) assay. Gene expression levels were detected by real-time quantitative polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…24 Qin et al found that miR-106a could decrease the sensitivity of colorectal cancer cells to 5-Fu. 25 In the present study, we found that knockdown of miR-486-5p enhanced the inhibitory effects of 5-Fu on the migration and invasion of PANC-1 cells. In addition, downregulation of miR-486-5p enhanced 5-Fuinduced apoptosis in PANC-1 cells in vitro.…”
Section: Discussionsupporting
confidence: 53%
“…24 Qin et al found that miR-106a could decrease the sensitivity of colorectal cancer cells to 5-Fu. 25 In the present study, we found that knockdown of miR-486-5p enhanced the inhibitory effects of 5-Fu on the migration and invasion of PANC-1 cells. In addition, downregulation of miR-486-5p enhanced 5-Fuinduced apoptosis in PANC-1 cells in vitro.…”
Section: Discussionsupporting
confidence: 53%
“…mir-106a-5p, also referred to as mir-106a, exerts an oncogenic role in different types of human cancer, including glioma (39,40). in addition, mir-106a facilitates radioresistance of prostate cancer (41) and promotes cell stemness of colorectal cancer (42). The results of the present study confirmed that mirna-106a-5p serves as an oncogene by augmenting TPTeP1-mediated stemness and radioresistance of glioma.…”
Section: Discussionsupporting
confidence: 78%
“…MicroRNAs (miRNAs) and long non-coding RNAs (lncRNAs), characterized by approximately 22 nucleotides (nt) and more than 200 nt, respectively, are the two main linear ncRNAs [11]. Previous studies have shown that miRNAs and lncRNAs are involved in tumorigenesis in several human cancers, including CRC, breast cancer, and lung cancer, by modulating mRNA expression of oncogenes or tumor inhibitory genes [12][13][14][15]. Unlike miRNAs and lncRNAs, circular RNA (circRNA) is a novel ncRNA with circular structure and without the 5' cap and 3' poly-A tail [16].…”
Section: Introductionmentioning
confidence: 99%